Self-Medication Practices Among MBBS Students: Evidence from Multan Medical and Dental College, Pakistan (Journal of Asian Development Studies, 2025)
Self-medication is a widespread practice among both the public and medical students in Pakistan. This study investigates the prevalence and patterns of self-medication among MBBS students at Multan Medical and Dental College. A structured questionnaire was administered to 200 randomly selected students across the first to fourth years, and data were analysed using SPSS version 20.0. Results indicate that students frequently self-medicate, primarily with analgesics, antipyretics, and antihistamines. The primary reasons identified include prior experience, time constraints, and cost savings. Although 87% of students reported no adverse effects, 13% experienced negative health outcomes. The study concludes that despite their medical knowledge, students often underestimate the risks of unsupervised drug use. Thus, policymakers must intervene to target awareness campaigns, introduce institutional reforms and enforce policy measures strictly to curb the trend of self-medication.